2012
DOI: 10.1007/978-1-62703-221-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Brown Algae as a Model for Plant Organogenesis

Abstract: Brown algae are an extremely interesting, but surprisingly poorly explored, group of organisms. They are one of only five eukaryotic lineages to have independently evolved complex multicellularity, which they express through a wide variety of morphologies ranging from uniseriate branched filaments to complex parenchymatous thalli with multiple cell types. Despite their very distinct evolutionary history, brown algae and land plants share a striking amount of developmental features. This has led to an interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 207 publications
2
18
0
Order By: Relevance
“…Nonetheless, evidence for phytohormone function in unicellular algae is beginning to accumulate, such as the role of abscisic acid and auxins in regulation of growth in unicellular green algae and diatoms ( Kobayashi et al 1997, Yoshida et al 2004, Park et al 2013, Lu et al 2014, Amin et al 2015. This is consistent with the hypothesis that hormones such as auxin might have served initially as growth-regulating hormones or pheromones in unicellular ancestors predating the advent of multicellularity (Cooke et al 2002, Bogaert et al 2013). While it is well established that algae (from cyanobacteria to brown algae) contain land plant phytohormones (reviewed in Tarakhovskaya et al 2007, Stirk and Van Staden 2014, Lu and Xu 2015, compounds such as auxins may be breakdown products or intermediates from tryptophan metabolism and have been detected also in unikonts (Bertilsson and Palmér 1972).…”
Section: Endogenous Signalingsupporting
confidence: 88%
“…Nonetheless, evidence for phytohormone function in unicellular algae is beginning to accumulate, such as the role of abscisic acid and auxins in regulation of growth in unicellular green algae and diatoms ( Kobayashi et al 1997, Yoshida et al 2004, Park et al 2013, Lu et al 2014, Amin et al 2015. This is consistent with the hypothesis that hormones such as auxin might have served initially as growth-regulating hormones or pheromones in unicellular ancestors predating the advent of multicellularity (Cooke et al 2002, Bogaert et al 2013). While it is well established that algae (from cyanobacteria to brown algae) contain land plant phytohormones (reviewed in Tarakhovskaya et al 2007, Stirk and Van Staden 2014, Lu and Xu 2015, compounds such as auxins may be breakdown products or intermediates from tryptophan metabolism and have been detected also in unikonts (Bertilsson and Palmér 1972).…”
Section: Endogenous Signalingsupporting
confidence: 88%
“…As summarized by Bogaert et al [20], brown algae and land plants, in spite of their phylogenetic distance, share many common developmental features. Both have an open-growth strategy, in which meristematic cells produce an unlimited sequence of new organs.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the results of this self-organization model with botanical data revealed that this hypothesis led to precise predictions as concerns the phyllotactic evolution during the whole ontogeny of a plant [17]. After this reminder we can turn to brown algae [18][19][20][21]. There are unfortunately relatively few quantitative measurements of the algae architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Despite promising technologies for molecular gene function analysis and forward genetics being developed recently (Farnham et al 2013), the use of fucoid algae in developmental biology has dwindled over the years, largely because of the poor amenability to genetic and molecular studies (Yang 2008). Because it is easily cultured (Vielhaben 1963;Müller 1962;Kumke 1973), Dictyota has been proposed as a possible model complementary to fucoids (Bogaert et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Studies focusing on brown algal eggs and fertilisation have resulted in important insights for plant system development (Bogaert et al 2013). Most of the research has focused on members of the Fucales.…”
Section: Introductionmentioning
confidence: 99%